(3JShjI efGRYGJ GdGSJKeGQ ai EWGQ GdbGfhf GdOhdi GdYGe (B: s (3OQGSI JMdjdjI ebGQfI (B/ s - (3YHOGdedc YHOGdQMef eMeO eWgQs; (3CTQa YQaGJ SdjeGf s; (3eMeO Thbi YHOGdYGd s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3JJMOK gPg GdQSGdI Yf JShjI efGRYGJ GdGSJKeGQ aj EWGQ GdbGfhf GdOhdj GdYGe ef GdfGMjJjf GdehVhYjI h GdELQGFjI habB dKdGKI feGPL JfXjejI RefjI (B: (3h HGdJGdj JchfJ GdQSGdI ef KdGKI CHhGH h aUd JegjOj (B: (3JfGhd GdeQcR GdOhdj cfehPL ELQGFj dJShjI efGRYGJ GdGSJKeGQq OhdI h eSJKeqQ ceG JfGhdJ GdOQGSI efXeI GdJLGQI GdYGdejI cfehPL ddJfXje GdcGed HLGfHjg GdELQGFj h GdehVhYj Ke JfGhd GJaGbjGJ GdGSJKeGQ GdOhdj h GdJWhQGJ GdCNjQI aj CMcGegG h GdJhLgGJ GdOhdjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2013s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B465-495s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3efGRYGJ GdGSJKeGQs; (3GdMeGjI GdOHdheGSjIs; (3efGRYGJ GdGSJKeGQs; (3GdJMcje GdJLGQjs; (3GdJMcjes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs